2007
DOI: 10.1080/10618560701525954
|View full text |Cite
|
Sign up to set email alerts
|

Water entrainment due to spillway surface jets

Abstract: Strong flow entrainment has been observed downstream of spillways constructed with flow deflectors. This water entrainment has important environmental and ecological impacts because it improves the mixing of powerhouse and spillway flows, but may negatively impact fish migration or create adverse flow conditions.Most studies found in the literature attempt to explain this entrainment with turbulent mixing. Both reduced-scale hydraulic models and single-phase, isotropic RANS models grossly under-predict the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…It is observed that surface jets attract water toward the jet region, a phenomenon called water entrainment. Turan et al (2007) described the main mechanisms causing water entrainment as acceleration of the surrounding fluid as the jets decelerates, surface currents, Coanda effect and the presence of bubbles.…”
Section: Hydrodynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is observed that surface jets attract water toward the jet region, a phenomenon called water entrainment. Turan et al (2007) described the main mechanisms causing water entrainment as acceleration of the surrounding fluid as the jets decelerates, surface currents, Coanda effect and the presence of bubbles.…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…Kinematic and dynamic boundary conditions as wells as turbulence quantities are programmed through UDFs. Details of the boundary conditions used for the Reynolds stress and velocity components are found in Turan et al (2007).…”
Section: Free Surface For the Rigid-lid Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is called water entrainment and has been reported in both field (Schneider & Wihelms 1996) and model studies (Fuller 1997). Turan et al (2007) studied the main mechanism causing water entrainment and recognized that spillway jet regimes strongly influence lateral currents and TDG distribution in the tailrace.…”
Section: Spillway Jet Regimesmentioning
confidence: 99%
“…Urban et al (2008) presented a model to predict TDG saturation just downstream of a spillway based on physical processes of mass transfer. The effects of bubble size distribution (Politano et al, (2007(Politano et al, ( , 2005(Politano et al, ( , 2003 and bubble volume and normal velocity fluctuation attenuation (Turan et al, 2007) have been studied to better understand and model air entrainment. Physically-based models have incorporated geometrical aspects of the dams such as stilling basin and river depths (Geldert et al, 1998), spillway configurations and flow parameters (Hibbs and Gulliver, 1997), upstream TDG concentration (Roesner and Norton, 1971), and flood discharge characteristics, such as water depths and pressures (Ran et al, 2009), to predict gas transfer and downstream TDG levels.…”
Section: Current Practices and Knowledgementioning
confidence: 99%